On Cooperation of Customs Administrations in the European Union and Serbia - Vranješ, Mile (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Cooperation of customs administrations between Member States of the European Union and cooperation of the Customs Administration of the Republic of Serbia with foreign customs administrations, regarding the efficient exchange of information is, most certainly, one of the important conventional measures for suppressing customs evasion and also a significant measure for increasing the efficiency of customs collection. Problems of information exchange regarding customs in the European Union has been regulated with two main instruments: Council Regulation 515/97, on mutual assistance between the administrative authorities of the Member States and cooperation between the latter and the Commission to ensure the correct application of the law on customs and agricultural matters and Council Directive 2010/24/EU concerning mutual assistance for the recovery of claims relating to taxes, duties and other measures. Additionally, the current multi-year program for customs in the European Union (Customs 2013) is contained in the Decision of the European Parliament and Council 624/207. Problems of information exchange regarding customs in the Republic of Serbia are regulated with one main instrument: Agreement on administrative assistance in customs matters of the Republic of Serbia and other countries.
Keywords: Serbia; European Union; customs; exchange of information; cooperation of customs administrations